Citizenship Rights and Technological Advancements: Navigating Obstacles And Seizing Opportunities in the Twenty-First Century - Kumar, Shailesh (Journal of Advanced Research in Political Science and Governance; Vol 7 No 2 (2023): Journal of Advanced Research in Political Science and Governance, 2023)
The 21st century has witnessed an unprecedented surge in technological advancements, revolutionizing the way societies function and individuals interact with the world. As we embrace the benefits of these innovations, the intricate relationship between technological progress and citizenship rights comes into focus. This review article delves into the challenges and opportunities that arise at the intersection of technology and citizenship rights, offering insights into the evolving landscape of governance, privacy, and civic engagement. Exploring digital citizenship, governance, and the transformative power of technology in reshaping civic life, the article navigates the nuances of privacy concerns, cybersecurity challenges, and the ethical considerations surrounding artificial intelligence. It also analyzes the role of citizens in the digital era, from leveraging social media for activism to confronting the dark underbelly of online engagement. In conclusion, the article emphasizes the imperative for thoughtful policies, ethical frameworks, and international collaboration to ensure that technological advancements align with the principles of justice and inclusivity, fostering a future where citizens’ rights are empowered rather than compromised.